Ảnh hưởng của bột polytetrafloetylen đến độ chống mài mòn của polyme nhiệt rắn trên cơ sở polyeste không no. - Thu, Nguyễn Minh; Diệu, Trần Vĩnh (Vietnam Journal of Chemistry, 2012)
Polytetrafluoethylene (PTFE) is a tough, flexible and no-resilient resistance to abrasive and wear. Therefore PTFE widely used as antifriction material for making bearings without smearing in machinery. Utilizing these advanced properties, the aim of this work is using PTFE powder to improve abrasive and wear resistance of unsaturated polyester based thermosetting polymer. In this work PTFE powder is commercial product with average dimension of particles about 200 - 400 mm without surface treatment. Three dispersion methods of PTFE powder in unsaturated polyester (UPE) have been studied, and it shows that the best method is immersing PTFE powder in mixture of acetone/styrene before mixing at speed of 2000 r/min for 60 min. The obtained material has good mechanical properties and low wear value. PTFE powder absorbs partly heat of curing reaction and decelerates curing process. At a ratio UPE/PTFE = 90/10 w.p., impact strength of material is 3.57 kJ/m2, wear value is lowest (0.0029 g), i.e. decreases 8.17 times in comparison with material without PTFE (0.0237 g).